Extraction optimization, characterization of microcrystalline cellulose from Theobroma cacao L. (Fam. Malvaceae) pod husks as binder - Arceo, Jan Dominik C.; Garcia, Kathrine Mae B.; Siringan, Nini Angelica T.; Ladignon, Ethel Andrea C. (​Manila: Department of Industrial Pharmacy, College of Pharmacy, University of the Philippines Manila, 2017)
Binders are pharmaceutical excipients which serve a critical function in tablet manufacturing by bringing formulation ingredients in a cohesive mix, with microcrystalline cellulose being generally considered to have the best binding properties. The pod husks of Theobroma cacao L. are normally thrown away after the processing of its beans, which presents a waste problem, but poses to provide a saleable commodity upon processing. Hence, further uses of these pod husks should be explored. This study involved the optimization of extraction temperatures of microcrystalline cellulose from Theobroma cacao L. pod husks, using extraction yield as the basis for determination. The extracted microcrystalline cellulose were characterized by subjecting it to physicochemical pharmacopoeial tests, phytochemical tests, and Fourier Transformed Infrared Spectroscopy. Furthermore, its binding properties through powder flow and water uptake characteristics, were compared with that of a commercially available microcrystalline cellulose. Optimized base and acid hydrolysis temperatures were 80±10°C with 11.41% w/w alpha-cellulose yield and 60±10°C with 89.47% w/w MCC, respectively, for a 10.21% MCC yield from dry pod husks. The extracted substance was characterized as microcrystalline cellulose with excellent flow properties and water-uptake capacities, as compared with the standard. This means that the extracted MCC could be employed as a tablet binder.
Available to the general public.
​Thesis (Bachelor of Science in Industrial Pharmacy)--University of the Philippines Manila, June 2017.
Keywords: Malvaceae; Cacao